Defining emergency telehealth. (September 2021) - Sikka, Neal; Gross, Hartmut; Joshi, Aditi U; Shaheen, Edward; Baker, Michael J; Ash, Adam; Hollander, Judd E; Cheung, Dickson S; Chiu, Alexander R; Wessel, Charles B; Robinson, Marcus; Lowry, Gregory; et al.
The American College of Emergency Physicians Emergency Telehealth Section was charged with development of a working definition of emergency telehealth that aligns with the College's definition of emergency medicine. A modified Delphi method was used by the section membership who represented telehealth providers in both private and public health-care delivery systems, academia and industry, rural and urban settings. Presented in this manuscript is the final definition of emergency telehealth developed with an additional six clarifying statements to address the context of the definition. Emergency telehealth is a core domain of emergency medicine and is inclusive of remotely providing all types of care for acute conditions of any kind requiring expeditious care irrespective of any prior relationship. The development of this definition is important to the global community of emergency physicians and all patients seeking acute care to ensure that appropriately trained clinicians are providing the highest quality of emergency services via the telehealth modality. We recommend implementing emergency telehealth in a manner that ensures appropriate qualifications of providers, appropriate/parity reimbursement for telehealth services and, most importantly, the delivery of quality care to patients in a safe, efficient, timely and cost-effective manner.